The impact of participating in basic medical insurance on depression scores of rural middle-aged and older adults—an empirical analysis based on CFPS data - Ziyin Liao; Rui Zhou; Jingwei Huang; Qing Wang; Jiajing Xu (Frontiers in Public Health)
IntroductionAccording to the latest research by the World Health Organization (WHO), the disease burden caused by depression has risen to the second place in the world, and will rise to the first place by 2030. Currently, there are approximately 90 million individuals with depression in China, with rural middle-aged and older adults facing higher risks due to factors such as weak economic foundations and poor health. This study empirically examines the effect of basic medical insurance in reducing depression scores (measured by the CES-D scale) among rural middle-aged and older adults and validates its underlying mechanisms.MethodsUsing panel data from the China Family Panel Studies (CFPS) in 2012 and 2018, this study constructs a two-way fixed effects model to analyze the relationship between basic medical insurance and depression scores. Heterogeneity analysis was conducted through grouped regression, while robustness checks were performed using panel Probit regression and Quantile regression. Additionally, moderation and mediation effect models were employed to analyze the mechanisms through which basic medical insurance reduces depression scores in this population.ResultsThe study finds that basic medical insurance has a positive effect on reducing depression scores among rural middle-aged and older adults. Grouped regression results reveal heterogeneity across subgroups, with weaker improvement effects observed among subgroups aged over 60, females, and those with spouses. By introducing an interaction term between insurance enrollment and chronic disease status into the baseline model, the study identifies a moderating effect of chronic disease on the depression-reducing impact of basic medical insurance. Mediation analysis using the three-step method and bootstrap approach demonstrates that household income per capita partially mediates this effect. Robustness checks support the main findings, and quantile regression indicates that the effect of basic medical insurance is most pronounced among individuals with mild depression or near-threshold depression scores.DiscussionThe research contributes to explaining the dynamic relationship between basic medical insurance and depression among rural middle-aged and older adults, enriching theoretical studies on the impact of basic medical insurance on mental health in this population. The findings hold significant theoretical implications.